SPECIFIC PROTEIN EXPRESSION OF GOAT PREIMPLANTATION EMBRYO IN VITRO AS AN EARLY PREGNANCY SIGNAL - Lanus Sumadiasa, I Wayan; Yuliani, Enny (Jurnal Veteriner, 2008)
The aim of the experiment was to investigate the intensity of signal secreted by embryos for their survival in the early pregnancy. Embryos at morulla and blastocyst stages generated by in vitro fertilization were frozen and then thawed for in vitro culture in tissue culture medium. The protein secreted by embryo were detected 48 hours after thawing for those frozen at morulla stage, and 24 hours and 72 hours after thawing for those frozen in the blastocyst stage. Results showed that preimplantation goat embryos secreted an average of 3,041 µg protein per ml medium for the embryo cultured in tissue culture medium (TCM) 199 + 0,1 % BSA and 1,992 µg protein per ml medium for embryo cultured in TCM without BSA. Non growing embryos secreted only a small amount protein, i.e. 0,434 µg protein per ml medium and 0,417 µg protein per ml medium respectively for embryo cultured TCM 199 with BSA and TCM without BSA. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed protein bands with many different molecular weight of 100, 95 , 55 , 43 , 28 and 18 KD. It appeared that the growing embryos secreted more proteins as compared to those non growing embryos.
Keywords: protein, goat, embryos, morulla, blastocyst, in vitro